Theoretical-methodological study of development of power-speed in climbing - Kozina, Z.; Ryepko, O. A.; Prusik, K.; Prusik, K.; Cieslicka, M. (Physical Education of Students, 2014)
Purpose: of the work was to develop theoretical and methodological foundations of power-speed in climbing. Material : 19 analyzed the literature on the problem of the relationship of the various components of speed-strength training. Results : the concept of speed-strength training climbers, which in its general form can be used at any stage of training. It was revealed that the components of the speed- force readiness (strength, speed and speed-strength endurance) are in an inverse relationship to each other. These dependences are hyperbolic. The relationships between strength, speed and the time limit for execution of work are summarized in the form of a hyperboloid. It is shown that the inverse relationship between the components of speed-strength readiness is a difficulty in the construction of the training process, as required in climbing all three aspects of speed strength training. The solution to this problem is the interchange of the funds allocated for the development of contradictory qualities. Conclusion : it is shown that there are particular manifestations of the various components of speed strength training of elite climbers, specializing in climbing to the complexity, speed, and mountain climbers.